Pemanfaatan Chatbot EVA dalam Meningkatkan Efektivitas Pelayanan Pelanggan pada Kopwan Atsiri - Zuraidah, Eva; Novayanti, Deasy; Sanwani, Sanwani; Sulthon, Besus Maula; Fadila, Ahmad Hasan; Rechal, Rechal; Putri, Chintya Amelia; Rivaldo, Ahmad; Kartini, Bunga (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Atsiri Women's Cooperative is a social community organization as a forum and means of developing every member of society that grows and develops on the basis of social awareness and responsibility from and for the community in the region, especially engaged in medium and small businesses. While the membership of the Atsiri Citayem Cooperative, hereinafter referred to as the Cooperative Mothers, is every member of the community. Atsiri Women's Cooperative, Established on December 11, 2011, is located at Jl. Jalan Sedap Malam Raya no 45 Rt 01 RW 12 Atsiri Permai Housing, Ragajaya Village, Bojonggede District. Bogor Regency. Postal Code 16920, engaged in the field of All Kinds of Business. The problem of limited understanding of social media management that has not been carried out in optimization in the UMKM management environment. The use of social media used is still manual for sales information. Artificial intelligence has become the main focus in the development of computer systems that have the ability to resemble the function of the human brain. One of them is the development and utilization of Chatbot Ecosystem Virtual Assistant (EVA) as a tool to help work in various fields and in Kopwan Atsiri, One of which is through further training activities on the use of information technology, online marketing, business management, and other relevant aspects. So that the training and socialization carried out do not stop only in the scope of meetings, but can also be applied by the community in their daily business activities. In this context, the training aims to evaluate the effectiveness of the type of Chatbot Ecosystem Virtual Assistant (EVA), in providing customer service at Kopwan Atsiri. Through the implementation of direct implementation of practicing Chatbot Ecosystem Virtual Assistant (EVA), which is the most efficient in the context of customer service. These results are expected to provide valuable insights for the development and implementation of Chatbot Ecosystem Virtual Assistant (EVA) in improving the effectiveness of customer service, as well as one solution in increasing knowledge, and making it easier to get fast information and provide a more accurate and strong understanding of efficiency.